Penerapan Model Pembelajaran Interaktif Tutor dalam Upaya Meningkatkan Partisipasi Belajar Peserta Didik Paket C di Homeschooling Kak Seto Surabaya - Alviyani, Sefti Dwi; Artha, I Ketut Atmaja Jhony (J+PLUS UNESA, 2023)
This research aims to 1) Describe the application of the Tutor Interactive Learning Model in increasing the learning participation of Package C students. 2) Assess the supporting factors. 3) Examine the inhibiting factors in the application of the Interactive Learning Model in an effort to increase students' learning participation. The approach and type used is descriptive qualitative, with the research location at Homeschooling Kak Seto Surabaya. Data collection techniques through in-depth interviews, participatory observation, and documentation. This research uses data analysis with data collection, data reduction, data presentation and then conclusion drawing. The results of this study indicate that the application of the Tutor Interactive Learning Model in an effort to increase the learning participation of Package C students goes well, as evidenced by the response and enthusiasm of students before and after school at Homeschooling Kak Seto Surabaya. Supporting factors include a fun and interactive classroom atmosphere, tutor creativity and adequate infrastructure. The inhibiting factors include bad mood, lack of confidence, laziness and network constraints.